2011
DOI: 10.1182/blood-2011-07-365932
|View full text |Cite
|
Sign up to set email alerts
|

Treating limited-stage nodular lymphocyte predominant Hodgkin lymphoma similarly to classical Hodgkin lymphoma with ABVD may improve outcome

Abstract: The appropriate therapy for limited-stage nodular lymphocyte predominant Hodgkin lymphoma (NLPHL) is unclear. In contrast to classical Hodgkin lymphoma (CHL), chemotherapy is often omitted; however, it is unknown whether this impacts the risk of relapse. Herein, we compared the outcome of patients with limitedstage NLPHL treated in an era in which ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) chemotherapy was routinely incorporated into the primary therapy to an earlier era in which radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 18 publications
6
48
0
1
Order By: Relevance
“…16,17 In contrast, a study from British Columbia reported that ABVD chemotherapy with or without RT improved outcomes compared with RT alone for limited stage NLPHL. 18 In our study, patients with early stages initially treated with CMT, chemotherapy or immuno-chemotherapy, achieved a good disease control, with a possible benefit over radiotherapy alone, a result that we can relate to a high rate of progression or relapse (26%) after initial radiotherapy. Chemotherapy alone has not been commonly used in adults with early stage NLPHL, 18 and is the main option for patients with advanced stage.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…16,17 In contrast, a study from British Columbia reported that ABVD chemotherapy with or without RT improved outcomes compared with RT alone for limited stage NLPHL. 18 In our study, patients with early stages initially treated with CMT, chemotherapy or immuno-chemotherapy, achieved a good disease control, with a possible benefit over radiotherapy alone, a result that we can relate to a high rate of progression or relapse (26%) after initial radiotherapy. Chemotherapy alone has not been commonly used in adults with early stage NLPHL, 18 and is the main option for patients with advanced stage.…”
Section: Discussionmentioning
confidence: 77%
“…18 In our study, patients with early stages initially treated with CMT, chemotherapy or immuno-chemotherapy, achieved a good disease control, with a possible benefit over radiotherapy alone, a result that we can relate to a high rate of progression or relapse (26%) after initial radiotherapy. Chemotherapy alone has not been commonly used in adults with early stage NLPHL, 18 and is the main option for patients with advanced stage. 7,8,19 In this study, patients with stages III-IV who were initially treated received mainly chemotherapy or immuno-chemotherapy (71.1%), a management which is consistent with the international guidelines.…”
Section: Discussionmentioning
confidence: 77%
“…In a retrospective report from the BCCA, no relapses were identified (median follow-up, ;5 years) in a subset of 14 patients treated with ABVD alone if an interim PET scan were normal. 45 Although these BCCA results are provocative, it is important to note that the follow-up is rather brief for this disease, which is often associated with late relapse.…”
Section: Chemotherapy Alonementioning
confidence: 97%
“…32,34,44 In contrast, a retrospective study from the BCCA comparing the outcome of 35 patients treated with RT alone with 51 patients treated with chemotherapy (usually ABVD [adriamycin, bleomycin, vinblastine, and dacarbazine]) with or without RT showed an improvement at 10 years in both PFS and OS, using a chemotherapy-based approach. 45 As with all the retrospective studies noted earlier, cautious interpretation is required because of different selection criteria, variable staging procedures, availability of supportive care, and substantial differences in duration of followup for the different therapies.…”
Section: Combined Modality Therapymentioning
confidence: 98%
“…A recent retrospective study suggested that treatment with ABVD might improve outcomes compared with radiation or observation. 30,31 T-cell/histiocyte-rich LBCL THRLBCL is a LBCL in which only scattered malignant cells are present in a background of lymphocytes, usually with single or small clusters of histiocytes (Figure 8). 32 The tumor cells may resemble the LP cells of NLPHL, but are more variable in size and shape, or may resemble centroblasts or immunoblasts or even HRS cells.…”
Section: Nodular Lymphocyte Predominant Hlmentioning
confidence: 99%